A Casa: arquitetura do texto - uma investigação sobre a origem do romance de Natércia Campos - Lima, Elisabete Sampaio Alencar (2009)
This research aims to understand the creation process of the novel A Casa (1999), by Natércia Campos, and present the results of the study of manuscripts and paratextual documents found in the writer’s collection. It assumes that three texts, "O espelho", "Infância no Minho" and "O Rastro" – with different structures and, probably, written at different times - contributed to the creation of the novel. This hypothesis gave a new direction to our work: no longer the original proposal of the genetic study of the novel A Casa, neither observing its writing process nor using the same methodology in book’s a theme. It applies some assumptions of Genetic criticism – whose object is the manuscript book and the aim is to raise hypotheses about the writer’s creation process, using the marks left in the writing path - for reading, transcription and interpretation of the documents that form the corpus . It presents the results.